Efektifitas Stimulasi Pijat Bayi terhadap Peningkatan Berat Badan Bayi Usia 0-4 Bulan dengan Riwayat BBLR - Reny Badariyah Ulfa; Zainal Munir; Kholisotin Kholisotin (Citra Delima : Jurnal Ilmiah STIKES Citra Delima Bangka Belitung, 2019)
Babies are very sensitive and delicate beings, needing to be fulfilled covering physical, biological and emotional needs. Such needs can be fulfilled through stimulation that not only gives a relaxing effect but also can stimulate growth by increasing the weight of the baby. The stimulation is done properly according to the guide steps of baby massage, it aims to achieve optimal growth. Know The effectiveness of the stimulus baby massage against the increase in weight of infants aged 0-4 months with a history of BBLR in the work area of Puskesmas Cermee. The design of the research used is quasi-experiment with One-Group Pre-Post Test Design Method. Sampling techniques for Accidental sampled with a sample number of 15 respondents. Data analysis is carried out with a sufficient analysis stage using an independent-Test with the level The significance of ρ -value < 0.05. The T-Test results showed that there was an influence on baby massage against increased baby weight with Increments of 3-20% with the value obtained t count = 11,183 > t-table = 2,144 and ρ-value 0.000 < 0.005. In low birth weight babies performed massage stimulation for 15 days that get intake of nutrients, breast milk, breast milk + formula milk and formula milk experienced a diverse weight gain of 3-20%.